Deep Learning in Vocational Education: A Quantitative Study of Teachers’ Readiness and Implementation Challenges in Lampung, Indonesia - Sari Indrayani; Hasan Hariri; Riswandi Riswandi; Handoko Handoko; Muhammad Mujtaba Asad (Journal of Pedagogy and Education Science, 2026)
This study aims to examine the readiness of vocational school teachers in Lampung to implement deep learning pedagogy and to identify the challenges they face in the process. A quantitative descriptive survey design was employed, with data collected from 1,000 public vocational school teachers using a structured questionnaire distributed via Google Forms, and analyzed through descriptive statistics in Microsoft Excel. The findings indicate that teachers demonstrated medium-to-high readiness, with strong results in access to technology (79%), digital competence (75%), integration and implementation (78%), and innovation and evaluation (77%), while collaboration and professional development were relatively weaker (71%), signaling the need for enhanced peer learning and sustained training. The novelty of this study lies in being among the first to map teacher readiness for deep learning pedagogy in vocational education, offering empirical evidence from a large-scale sample. The results have practical implications for policymakers and school leaders to strengthen digital infrastructure, expand professional development programs, and foster collaborative practices that support sustainable adoption of deep learning. Overall, this study contributes to the global literature by confirming teacher readiness as a decisive factor for the successful implementation of deep learning pedagogy and provides context-specific insights to inform future policy and practice in vocational education.